Ceramic sheet and preparation method thereof
By using the preparation raw materials and gel injection molding process with specific ratios, the problems of excessive adhesive use and high production cost in the preparation of ceramic thin plates are solved, and the high performance and low cost preparation of ceramic thin plates are achieved.
Patent Information
- Application Number
- CN202411790985.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-06
- Publication Date
- 2025-03-07
AI Technical Summary
The existing ceramic thin plate preparation methods have problems such as high sintering shrinkage, poor dimensional accuracy and performance due to excessive use of adhesives, and high production costs and difficult to achieve ceramic thin plates with high flatness and flexural strength, fracture toughness and hardness.
Preparation materials with specific composition and proportions are prepared, including ceramic powder, sintering aids, organic monomers, crosslinking agents, dispersants, plasticizers, initiators and catalysts, and curing, demolding, drying, glue discharge and sintering are carried out through the gel injection molding process to regulate the polymerization rate and the toughness of the wet blank after curing.
A ceramic thin plate with high flatness, bending strength not less than 675MPa, fracture toughness not less than 5.74MPa·m1/2 and hardness not less than 17.60GPa is achieved, while reducing production costs and improving molding efficiency.
Smart Images

Figure CN119569466A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of ceramic composite materials, and in particular to a ceramic thin plate and a preparation method thereof. Background Art
[0002] The internal microstructure and stress distribution of the ceramic green body after forming will affect its strength and the performance of the finished product obtained after final sintering. Currently, ceramic thin plates (about 3mm) used in the field of electronic products can be formed by dry pressing and isostatic pressing, and then obtained by subsequent grinding; while thin plates with lower thickness (≤1mm) can be prepared by tape casting.
[0003] However, the tape casting method for preparing ceramic thin plates has the following disadvantages: During the tape casting process, about 20% of the binder is required to ensure the molding and stability of the material. The use of the above-mentioned binder content will cause the product to have a large shrinkage rate during the subsequent sintering process, affecting the dimensional accuracy and overall performance of the product, and requiring additional processing and trimming to meet the design requirements. In addition, the tape casting equipment and process are relatively complex, resulting in high production costs, which will limit the application of the tape casting method in certain low-cost or large-scale production scenarios.
[0004] The preparation of ceramic thin plates by dry pressing and isostatic pressing has the following disadvantages: dry pressing and isostatic pressing are difficult to form thinner (≤1mm) green bodies, and relatively thick green bodies need to be obtained to avoid cracking; and a certain amount of raw material waste will occur during the process of large-scale processing (such as CNC cutting, grinding and polishing, etc.) of the thick green bodies to achieve the required size and surface quality, thereby reducing material utilization.
[0005] Furthermore, it is difficult to obtain a ceramic thin plate with high flatness, high bending strength, fracture toughness and hardness by the above method.
[0006] In view of this, the present invention is proposed. Summary of the invention
[0007] The object of the present invention is to provide a ceramic thin plate and a preparation method thereof, so as to solve or improve the above technical problems.
[0008] The present invention can be implemented like this:
[0009] In a first aspect, the present invention provides a method for preparing a ceramic thin plate, comprising the following steps: injecting a raw material for preparing the ceramic thin plate into a mold, followed by curing, demoulding, drying, debinding and sintering;
[0010] The raw materials for preparation include slurry raw materials, initiators and catalysts; the slurry raw materials include powder raw materials and premixed liquids; the powder raw materials include ceramic powders and sintering aids; the premixed liquid includes organic monomers, crosslinking agents, dispersants, plasticizers and solvents;
[0011] The mass of the powder raw material is 60% to 77% of the slurry raw material;
[0012] The mass of the sintering aid in the powder raw material is 2% to 7%, and the balance is ceramic powder;
[0013] The mass of the organic monomer is 14% to 25% of the premixed liquid, the mass ratio of the organic monomer to the crosslinking agent is 20:1 to 70:1, the mass of the dispersant is 0.5% to 1.6% of the powder raw material, and the mass of the plasticizer is 2% to 3.3% of the slurry raw material;
[0014] The mass of the initiator is 0.045% to 0.096% of the slurry raw material, and the mass of the catalyst is 0.020% to 0.102% of the slurry raw material.
[0015] In an optional embodiment, the ceramic powder includes at least one of silicon nitride, silicon carbide, aluminum oxide, aluminum nitride, iron oxide, chromium oxide, and zirconium oxide;
[0016] and / or, the sintering aid comprises at least one of magnesium oxide, yttrium oxide, titanium oxide, silicon oxide, calcium oxide and strontium oxide;
[0017] and / or, the organic monomer comprises at least one of dimethylacrylamide, acrylamide, methacrylamide and hydroxymethylacrylamide;
[0018] and / or, the cross-linking agent comprises at least one of methylene acrylamide, methyl acryl acrylate, and poly(ethylene glycol) dimethacrylate;
[0019] and / or, the dispersant comprises at least one of ammonium polyacrylate, polyethylene glycol, citrate, polyetherimide, diethylene glycol, ethylene glycol ethyl ether, sodium lauryl sulfate, sodium hexametaphosphate and polyvinyl pyrrolidone;
[0020] and / or, the plasticizer comprises at least one of phthalates, stearates and citrates;
[0021] and / or, the initiator comprises at least one of ammonium persulfate, benzoyl peroxide, tert-butyl hydroperoxide and azobisisobutyronitrile;
[0022] And / or, the catalyst includes at least one of tetramethylethylenediamine, β-naphthalenesulfonic acid formaldehyde condensate and 2,2′-azo[2-(2-imidazolin-2-yl)propane]dihydrochloride.
[0023] In an optional embodiment, the preparation of the powder raw material includes: wet ball milling a mixture of ceramic powder and sintering aid, and drying.
[0024] In an optional embodiment, the ball milling speed is 200 r / min to 320 r / min, and the ball milling time is 15 h to 24 h.
[0025] In an alternative embodiment, the mixture of ceramic powder and sintering aid is first subjected to a first wet ball milling and a first drying, then sintered, and then subjected to a second wet ball milling and a second drying.
[0026] In an optional embodiment, the sintering temperature is 1000° C. to 1300° C., and the sintering time is 3 h to 5 h.
[0027] In an optional embodiment, the preparation of the slurry raw material includes: mixing part of the powder raw material with the premixed liquid for the first time and degassing, and then adding the remaining powder raw material for the second time mixing and degassing.
[0028] In an optional embodiment, the first mixing is performed at 1150 r / min to 1450 r / min for 3 min to 5 min.
[0029] In an optional embodiment, the second mixing is performed at 1500 r / min to 1800 r / min for 5 min to 8 min.
[0030] In an optional embodiment, the powder raw materials used in the first mixing account for 1 / 2 to 2 / 3 of all the powder raw materials.
[0031] In an optional embodiment, the mold includes an upper mold and a lower mold that match each other;
[0032] The lower mold is provided with a groove, and the upper mold is provided with a through hole, so that after the upper mold and the lower mold are closed, the groove and the through hole cooperate to form a casting cavity for accommodating the prepared raw materials, and the open part of the through hole away from the groove is used to inject the prepared raw materials.
[0033] In an optional embodiment, the roughness of the surface of the lower mold for contacting the prepared raw material is 2.1μm to 5.8μm, the roughness of the surface of the lower mold for contacting the upper mold is 7.3μm to 13.2μm; the roughness of the surface of the upper mold for contacting the lower mold is 7.3μm to 13.2μm.
[0034] In an optional embodiment, the groove wall of the groove has a smooth hydrophobic layer.
[0035] In an optional embodiment, the curing is performed at 28° C. to 42° C. and 1 torr to 10 torr for 6 min to 12 min.
[0036] In an optional embodiment, drying includes: using a liquid desiccant to dehydrate the wet blank obtained by demolding.
[0037] In an alternative embodiment, the liquid desiccant comprises at least one of polyethylene glycol, ethanol, acetone, glycerol, 1,2-propylene glycol and diethylene glycol.
[0038] In an optional embodiment, the wet blank is first placed in a first liquid desiccant for 2 hours to 6 hours, and then placed in a second liquid desiccant for 2 hours to 6 hours, and then the liquid desiccant is removed to obtain a green blank; wherein the concentration of the first liquid desiccant is less than the concentration of the second liquid desiccant.
[0039] In an optional embodiment, the ratio of the mass of the liquid desiccant used in each drying to the mass of the wet blank is 1.21:1 to 2.47:1.
[0040] In an optional embodiment, the debinding includes: firstly performing the debinding at 230°C to 340°C for 2h to 3h, then performing the debinding at 500°C to 625°C for 2h to 3h, and then performing the debinding at 780°C to 820°C for 2h to 3h;
[0041] In an optional embodiment, the temperature is increased to 230° C. to 340° C. at a heating rate of 1° C. / min to 3° C. / min.
[0042] In an optional embodiment, the temperature is increased to 500° C. to 625° C. at a heating rate of 0.5° C. / min to 1° C. / min.
[0043] In an optional embodiment, the sintering is performed under the condition of 2MPa to 6MPa.
[0044] In an alternative embodiment, the sintering atmosphere is a vacuum or an inert atmosphere.
[0045] In a second aspect, the present invention provides a ceramic thin plate prepared by the preparation method of any one of the aforementioned embodiments.
[0046] In an optional embodiment, the thickness of the ceramic thin plate is ≤3 mm.
[0047] In an optional embodiment, the flexural strength of the ceramic thin plate is not less than 675 MPa.
[0048] In an optional embodiment, the fracture toughness of the ceramic thin plate is not less than 5.74 MPa·m 1 / 2 .
[0049] In an optional embodiment, the hardness of the ceramic thin plate is not less than 17.60 GPa.
[0050] The beneficial effects of the present invention include:
[0051] The present invention adopts raw materials with specific composition and ratio to slow down the polymerization rate of monomers and cross-linking agents, improve the toughness of wet blanks after curing, and obtain ceramic thin plates with high flatness, high bending strength, fracture toughness and hardness. In addition, the method can realize rapid pulling of the upper mold, improve demoulding efficiency, and reduce production costs. BRIEF DESCRIPTION OF THE DRAWINGS
[0052] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.
[0053] Figure 1 A schematic diagram of the structure of the lower mold in the mold provided by the present invention;
[0054] Figure 2 A schematic diagram of the top structure of the upper mold in the mold provided by the present invention;
[0055] Figure 3 This is a schematic diagram of the bottom structure of the upper mold in the mold provided by the present invention.
[0056] Icon: 100 - lower die; 110 - groove; 120 - upper surface of lower die; 200 - upper die; 210 - through hole; 220 - lower surface of upper die. DETAILED DESCRIPTION
[0057] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.
[0058] The ceramic thin plate and the preparation method thereof provided by the present invention are described in detail below.
[0059] The present invention provides a method for preparing a ceramic thin plate, comprising the following steps: injecting a raw material for preparing the ceramic thin plate into a mold (such as Figures 1 to 3 ), followed by curing, demoulding, drying, debinding and sintering.
[0060] The raw materials include slurry raw materials, initiators and catalysts, which are added when the slurry is injected into the mold.
[0061] The slurry raw materials include powder raw materials and premixed liquid. The powder raw materials include ceramic powder and sintering aid. The premixed liquid includes organic monomer, crosslinking agent, dispersant, plasticizer and solvent.
[0062] In some optional embodiments, the mass of the powder raw material can be 60% to 77% of the slurry raw material, such as 60%, 62%, 65%, 68%, 70%, 72%, 75% or 77%, etc., or other values within the range of 60% to 77%.
[0063] In some optional embodiments, the mass of the sintering aid in the powder raw material can be 2% to 7%, such as 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5% or 7%, etc., or other values within the range of 2% to 7%. In the powder raw material, except for the content of the sintering aid, the remainder is the content of the ceramic powder.
[0064] In some optional embodiments, the mass of the organic monomer can be 14% to 25% of the premix, such as 14%, 15%, 16%, 17%, 18%, 19%, 20%, 21%, 22%, 23%, 24% or 25%, etc., or other values within the range of 14% to 25%.
[0065] The mass ratio of the organic monomer to the crosslinking agent can be 20:1 to 70:1, such as 20:1, 25:1, 30:1, 35:1, 40:1, 45:1, 50:1, 55:1, 60:1, 65:1 or 70:1, or other values within the range of 20:1 to 70:1.
[0066] The mass of the dispersant can be 0.5% to 1.6% of the powder raw material, such as 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5% or 1.6%, etc., or other values within the range of 0.5% to 1.6%.
[0067] The mass of the plasticizer can be 2% to 3.3% of the slurry raw material, such as 2%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, 3.0%, 3.1%, 3.2% or 3.3%, etc., or other values within the range of 2% to 3.3%.
[0068] The mass of the initiator can be 0.045% to 0.096% of the slurry raw material, such as 0.045%, 0.05%, 0.055%, 0.06%, 0.065%, 0.07%, 0.075%, 0.08%, 0.085%, 0.09%, 0.095% or 0.096%, etc., or other values within the range of 0.045% to 0.096%.
[0069] The mass of the catalyst can be 0.020% to 0.102% of the slurry raw material, such as 0.020%, 0.025%, 0.03%, 0.04%, 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, 0.10% or 0.102%, etc., or other values within the range of 0.020% to 0.102%.
[0070] In some optional embodiments, the ceramic powder may illustratively but not limitatively include at least one of silicon nitride, silicon carbide, aluminum oxide, aluminum nitride, iron oxide, chromium oxide and zirconium oxide.
[0071] The sintering aid may illustratively but not limitatively include at least one of magnesium oxide, yttrium oxide, titanium oxide, silicon oxide, calcium oxide, and strontium oxide.
[0072] The organic monomer may illustratively but not limitatively include at least one of dimethylacrylamide, acrylamide, methacrylamide, and hydroxymethylacrylamide.
[0073] The cross-linking agent may illustratively but not limitatively include at least one of methylene acrylamide, acryl methyl acrylate, and poly(ethylene glycol) dimethacrylate.
[0074] The dispersant may illustratively but not limitatively include at least one of ammonium polyacrylate, polyethylene glycol, citrate, polyetherimide, diethylene glycol, ethylene glycol ethyl ether, sodium lauryl sulfate, sodium hexametaphosphate, and polyvinyl pyrrolidone.
[0075] The plasticizer may exemplarily but not limitatively include at least one of phthalates, stearates, and citrates, wherein the phthalate plasticizer may include dibutyl phthalate, and the citrate plasticizer may include acetyl tributyl citrate.
[0076] The initiator may illustratively but not limitatively include at least one of ammonium persulfate, benzoyl peroxide, tert-butyl hydroperoxide, and azobisisobutyronitrile.
[0077] The catalyst may illustratively but not limitatively include at least one of tetramethylethylenediamine, β-naphthalenesulfonic acid formaldehyde condensate, and 2,2′-azo[2-(2-imidazolin-2-yl)propane]dihydrochloride.
[0078] As mentioned above, in the gel casting system for preparing raw materials provided above, by mixing initiator and catalyst components, a molding process with controllable curing time is obtained; at the same time, a small amount of plasticizer is introduced into the slurry to slow down the polymerization rate of organic monomers and crosslinking agents, improve the toughness of the wet blank after curing, and obtain a ceramic thin plate with high bending strength, fracture toughness and hardness. In addition, the gel casting system can also realize rapid pulling of the upper mold 200, so that the wet blank with a thickness of 1mm to 3mm can withstand slight pulling during demolding and be demolded quickly, which is conducive to improving demolding efficiency.
[0079] In some optional embodiments, the preparation of the powder raw material includes: wet ball milling a mixture of ceramic powder and sintering aid, and drying.
[0080] The ball milling speed may be 200 r / min to 320 r / min, such as 200 r / min, 240 r / min, 260 r / min, 280 r / min, 290 r / min, 300 r / min, 310 r / min or 320 r / min, or other values within the range of 200 r / min to 320 r / min. During the wet ball milling process, an appropriate amount of anhydrous ethanol may be used.
[0081] The ball milling time can be 15 h to 24 h, such as 15 h, 16 h, 18 h, 20 h, 22 h or 24 h, etc., or other values within the range of 15 h to 24 h.
[0082] In some preferred embodiments, the mixture of ceramic powder and sintering aid can be first wet ball milled and dried for the first time, then sintered, and then wet ball milled for the second time and dried for the second time. The sintering temperature can be 1000°C to 1300°C, such as 1000°C, 1050°C, 1100°C, 1150°C, 1200°C, 1250°C or 1300°C, or other values within the range of 1000°C to 1300°C. The sintering time can be 3h to 5h, such as 3h, 3.5h, 4h, 4.5h or 5h, or other values within the range of 3h to 5h.
[0083] Pre-sintering the ceramic powder and the sintering aid helps to make the ceramic powder more evenly mixed in the subsequent mixing process, and helps to improve the density and uniformity after subsequent sintering.
[0084] In some optional embodiments, the preparation of the slurry raw material may include: mixing part of the powder raw material with the premixed liquid for the first time and degassing, and then adding the remaining powder raw material for the second time mixing and degassing.
[0085] The first mixing and the second mixing can both be carried out in a planetary vacuum deaerator.
[0086] Among them, the first mixing can be carried out at 1150r / min~1450r / min (such as 1150r / min, 1200r / min, 1250r / min, 1300r / min, 1350r / min, 1400r / min or 1450r / min, etc.) for 3min~5min (such as 3min, 3.5min, 4min, 4.5min or 5min, etc.).
[0087] The second mixing can be carried out at 1500r / min~1800r / min (such as 1500r / min, 1550r / min, 1600r / min, 1650r / min, 1700r / min, 1750r / min or 1800r / min, etc.) for 5min~8min (such as 5min, 5.5min, 6min, 6.5min, 7min, 7.5min or 8min, etc.).
[0088] In some optional embodiments, the powder raw materials used in the first mixing may account for 1 / 2 to 2 / 3 of all the powder raw materials.
[0089] Through the above two mixing and degassing steps, a uniform and fine slurry can be obtained.
[0090] In the present invention, combined with Figures 1 to 3 The mold includes an upper mold 200 and a lower mold 100 that match each other; the lower mold 100 is provided with a groove 110, and the upper mold 200 is provided with a through hole 210, so that after the upper mold 200 and the lower mold 100 are molded together, the groove 110 and the through hole 210 cooperate to form a casting cavity for accommodating the prepared raw materials, and the open part of the through hole 210 away from the groove 110 is used to inject the prepared raw materials.
[0091] During injection molding, the upper mold 200 and the lower mold 100 are stacked in order from top to bottom.
[0092] The shapes of the grooves 110 and through holes 210 match the shape of the ceramic thin plate to be prepared. Specifically, the shapes of the grooves 110 and through holes 210 can be designed according to actual needs, and the sizes of the grooves 110 and through holes 210 are processed according to the shrinkage rate after the green body is solidified, dried and sintered.
[0093] In some optional embodiments, the roughness of the surface of the lower mold 100 for contacting the raw material can be 2.1 μm to 5.8 μm (such as 2.1 μm, 2.5 μm, 3 μm, 3.5 μm, 4 μm, 4.5 μm, 5 μm, 5.5 μm or 5.8 μm, etc.). The roughness of the surface of the lower mold 100 for contacting the upper mold 200 (defined as the lower mold upper surface 120) can be 7.3 μm to 13.2 μm (such as 7.3 μm, 8 μm, 8.5 μm, 9 μm, 9.5 μm, 10 μm, 10.5 μm, 11 μm, 11.5 μm, 12 μm, 12.5 μm, 13 μm or 13.2 μm, etc.). Similarly, the roughness of the surface of the upper mold 200 for contacting the lower mold 100 (defined as the upper mold lower surface 220) can be 7.3μm to 13.2μm (such as 7.3μm, 8μm, 8.5μm, 9μm, 9.5μm, 10μm, 10.5μm, 11μm, 11.5μm, 12μm, 12.5μm, 13μm or 13.2μm, etc.). Specifically, the roughness of the lower mold upper surface 120 is equal to the roughness of the upper mold lower surface 220.
[0094] In some preferred embodiments, sealing silicone grease is evenly applied on the contact surface between the lower mold 100 and the upper mold 200 .
[0095] In some preferred embodiments, the groove wall of the groove 110 has a smooth hydrophobic layer. For example, silicone oil can be evenly applied to the groove wall of the groove 110, and then heated at 50°C to 60°C for 15min to 20min to form a smooth hydrophobic layer.
[0096] By controlling the roughness of different surfaces, applying sealing silicone grease on the contact surfaces of the upper mold 200 and the lower mold 100, and providing a smooth hydrophobic layer on the groove wall of the groove 110, demoulding can be facilitated, demoulding efficiency can be improved, and costs can be reduced.
[0097] As mentioned above, the use of a mold with the above structure to prepare a ceramic thin plate does not require the use of a special release agent, which greatly improves the efficiency and cost of demolding. In addition, when demolding, the wet blank is subjected to uniform force at all locations and is not easily damaged or cracked; the through hole 210 has a large opening, and the injection molding method is simple and easy, and only the prepared raw materials need to be poured into the casting cavity. In addition, after demolding, only a simple cutting process is required to remove the excess parts around the thin plate to obtain a complete wet blank, and the processing difficulty is relatively low.
[0098] Before injection molding, the mold is cleaned and dried, the lower mold 100 is placed flat, the sealing silicone grease is evenly applied to the contact surface of the lower mold 100 and the upper mold 200, and the upper mold 200 is placed on the surface of the lower mold 100 coated with silicone grease, and the outer edges are aligned. Subsequently, initiators and catalysts are added to the prepared slurry raw materials, and the planetary vacuum degassing machine is turned on, the speed is set to 1200r / min~1400r / min, and rotated for 8s~20s, and then taken out and poured into the groove 110 in the lower mold 100. When the material liquid level is slightly higher than the upper surface of the through hole 210 of the upper mold 200, the pouring is stopped.
[0099] In some optional embodiments, curing can be carried out at 28°C to 42°C (such as 28°C, 30°C, 32°C, 34°C, 36°C, 38°C, 40°C or 42°C, etc.), 1torr to 10torr (such as 1torr, 2torr, 4torr, 6torr, 8torr or 10torr, etc.) for 6min to 12min (such as 6min, 8min, 10min or 12min, etc.). The process can be carried out in a vacuum drying oven.
[0100] After the prepared raw materials are gelled, the mold is taken out of the vacuum drying oven. Since the liquid level of the prepared raw materials is higher than the surface of the through hole 210 of the upper mold 200 during pouring, this part of the prepared raw materials is bonded to the upper surface of the through hole 210 after solidification, and is evenly distributed and has a certain strength. The wet elastomer blank that is not completely dried can be completely demolded by simply lifting the upper mold 200 in the vertical direction.
[0101] Furthermore, after the excess part of the wet blank is cut, a drying process is performed, and the drying process includes: using a liquid desiccant to dehydrate the wet blank obtained by demolding. The liquid desiccant may exemplarily but not limitatively include at least one of polyethylene glycol, ethanol, acetone, glycerol, 1,2-propylene glycol and diethylene glycol.
[0102] In some preferred embodiments, the wet blank can be placed in a first liquid desiccant for 2 hours to 6 hours, and then placed in a second liquid desiccant for 2 hours to 6 hours, and then the liquid desiccant is removed to obtain a thin plate green blank without obvious deformation; wherein the concentration of the first liquid desiccant is less than the concentration of the second liquid desiccant.
[0103] The ratio of the mass of the liquid desiccant used in each drying to the mass of the wet blank can be 1.21:1 to 2.47:1, such as 1.21:1, 1.5:1, 1.8:1, 2:1, 2.2:1 or 2.47:1, or other values within the range of 1.21:1 to 2.47:1.
[0104] As mentioned above, since the solidification is carried out in a vacuum environment, oxygen inhibition caused by contact between oxygen in the air and the slurry is avoided, so that the surface of the solidified green body does not have serious delamination and cracking. At the same time, since the vacuum environment isolates the moisture that quickly escapes from the surface of the green body in the box, the rate of the first drying stage of the wet green body is slowed down, and the problem of deformation caused by the inconsistent moisture dissipation rate inside and on the surface of the green body in the early stage is alleviated to a certain extent. Further, after the green body is solidified, it is dried in a liquid desiccant (such as ethanol) environment. Ethanol is soluble in water and has a similar density. It can be replaced by using the osmotic pressure of water in ethanol that is greater than the osmotic pressure inside the green body, which slows down the stress unevenness caused by the inconsistent shrinkage of various parts of the green body, and further suppresses the deformation trend of the green body. In addition, different concentrations of ethanol have different replacement rates for the water inside the green body. The higher the concentration, the greater the osmotic pressure, the higher the rate of water loss in the green body, and the more likely it is to crack. Therefore, it is first dried slowly in a relatively low concentration ethanol environment. After most of the water is replaced and dissipated, the remaining water is completely replaced at a higher concentration, and finally the green body is placed in a constant temperature and humidity environment to completely evaporate the ethanol. The method of drying with a concentration gradient liquid can greatly increase the green body drying cycle, reduce the placement time of the green body in a constant temperature and humidity environment, and greatly improve production efficiency.
[0105] In some optional embodiments, the debinding may include: first performing the debinding at 230°C to 340°C (such as 230°C, 250°C, 280°C, 300°C, 320°C or 340°C, etc.) for 2h to 3h (such as 2h, 2.5h or 3h, etc.), then performing the debinding at 500°C to 625°C (such as 500°C, 520°C, 540°C, 560°C, 580°C, 600°C or 625°C, etc.) for 2h to 3h (such as 2h, 2.5h or 3h, etc.), and then performing the debinding at 780°C to 820°C (such as 780°C, 790°C, 800°C, 810°C or 820°C, etc.) for 2h to 3h (such as 2h, 2.5h or 3h, etc.).
[0106] In some optional embodiments, the temperature can be increased to 230°C to 340°C at a heating rate of 1°C / min to 3°C / min (such as 1°C / min, 1.5°C / min, 2°C / min, 2.5°C / min or 3°C / min, etc.).
[0107] The temperature can be increased to 500°C to 625°C at a heating rate of 0.5°C / min to 1°C / min (such as 0.5°C / min, 0.6°C / min, 0.7°C / min, 0.8°C / min, 0.9°C / min or 1°C / min, etc.).
[0108] In some optional embodiments, sintering can be performed under the condition of 2MPa to 6MPa (such as 2MPa, 3MPa, 4MPa, 5MPa or 6MPa, etc.).
[0109] The sintering atmosphere is a vacuum atmosphere or an inert atmosphere (such as a nitrogen atmosphere or an argon atmosphere).
[0110] As mentioned above, the method for producing ceramic thin plates provided by the present invention can reduce costs while simplifying the demolding method, improving the curing and drying efficiency, and obtaining complete ceramic thin plate green bodies without deformation or warping. By combining the subsequent debinding and sintering system, a finished ceramic thin plate with small processing volume and high flatness can be obtained.
[0111] Correspondingly, the present invention also provides a ceramic thin plate, which is prepared by the above preparation method.
[0112] The ceramic thin plate can be applied to electronic product structural parts or household appliance appearance parts by way of example.
[0113] In some optional embodiments, the thickness of the ceramic thin plate is ≤3 mm.
[0114] In some optional embodiments, the flexural strength of the ceramic thin plate is not less than 675 MPa.
[0115] In some optional embodiments, the fracture toughness of the ceramic thin plate is not less than 5.74 MPa·m 1 / 2 .
[0116] In some optional embodiments, the hardness of the ceramic thin plate is not less than 17.60 GPa.
[0117] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.
[0118] Example 1
[0119] This embodiment provides a ceramic thin plate, and the preparation method thereof includes:
[0120] S1: preparing powder raw materials.
[0121] Take 96.32g of silicon nitride powder with a particle size of 0.3-1.2μm, 14.68g of silicon powder with a particle size of 0.5-0.9μm, and 2.51g of sintering aid (magnesium oxide and yttrium oxide mixed in a mass ratio of 2:3) and anhydrous ethanol for the first wet ball milling, the ball-to-material ratio is 1.8:1, the speed is set to 260r / min, and the ball milling time is 10h to obtain the first ball milling material. After the first ball milling material is dried, the second wet ball milling is carried out, the ball-to-material ratio is 1.8:1, the speed is set to 200r / min, and the ball milling time is 5h to obtain the second ball milling material. After the second ball milling material is dried, it is passed through a 120-mesh sieve for standby use.
[0122] The total amount of the above powder raw materials is 113.51 g, of which the mass percentage of the sintering aid is about 2.21% and the mass percentage of the ceramic powder is about 97.79%.
[0123] S2: preparing slurry raw materials.
[0124] 5g of dimethylacrylamide (organic monomer), 0.25g of methylene acrylamide (crosslinking agent), 0.68g of ammonium polyacrylate (dispersant), 2.15g of dibutyl phthalate (plasticizer), 1.41g of acetyl tributyl citrate (plasticizer) and 25.51g of deionized water (solvent) were put into a beaker, and mixed evenly at room temperature using a stirrer to obtain a premixed liquid. 75.67g of the powder raw material and all the premixed liquid were poured into a container, placed in a planetary vacuum deaerator for the first mixing and deaeration for 5min, and the speed was set to 1350r / min; then, all the remaining powder raw materials were poured into the container for the second mixing and deaeration for 7min, and the speed was set to 1550r / min; a slurry raw material with a solid content of about 50vol% was obtained.
[0125] The mass of the above-mentioned premix is 35g, the mass of the slurry raw material is 148.51g, and the powder raw material is approximately 76.43% of the slurry raw material; the mass of the organic monomer is approximately 14.29% of the premix, the mass ratio of the organic monomer to the cross-linking agent is 20:1, the mass of the dispersant is approximately 0.6% of the powder raw material, and the mass of the plasticizer is approximately 2.4% of the slurry raw material.
[0126] S3: Mould preparation.
[0127] like Figures 1 to 3 As shown, the mold includes an upper mold 200 and a lower mold 100 that match each other; the lower mold 100 is provided with a groove 110, and the upper mold 200 is provided with a through hole 210, so that after the upper mold 200 and the lower mold 100 are molded together, the groove 110 and the through hole 210 cooperate to form a casting cavity for accommodating the prepared raw materials, and the open part of the through hole 210 away from the groove 110 is used to inject the prepared raw materials.
[0128] The upper mold 200 and the lower mold 100 are stacked in order from top to bottom, and the shapes of the groove 110 and the through hole 210 match the shape of the ceramic thin plate to be prepared. The roughness of the surface of the lower mold 100 for contacting the raw material is 3.5 μm, the roughness of the upper surface 120 of the lower mold is 7.3 μm, and the roughness of the lower surface 220 of the upper mold is 8.5 μm.
[0129] The mold is cleaned and dried, and silicone oil is evenly applied to the groove wall of the groove 110 of the lower mold 100, and heated to 60°C in an oven for 30 minutes to prepare a smooth hydrophobic layer. The lower mold 100 is placed on a flat, non-inclined plane, and sealing silicone grease is evenly applied to the surface where the lower mold 100 contacts the upper mold 200; the upper mold 200 is placed on the surface of the lower mold 100 coated with silicone grease, and the outer edges are aligned, and placed in a vacuum drying oven.
[0130] S4: injection molding and curing.
[0131] Dissolve 0.14g of benzoyl peroxide (initiator) and 0.03g of tetramethylethylenediamine (catalyst) in 2ml of deionized water, pour into the above slurry raw material, turn on the vacuum degassing machine, set the speed to 1200r / min, and after 10s of mixing and degassing, immediately pour into the groove 110 of the lower mold 100. When the liquid level rises to a level slightly higher than the upper surface of the through hole 210 of the upper mold 200, stop pouring; close the vacuum drying oven door, set the temperature to 35°C; open the vacuum valve and vacuum pump, and when the vacuum degree in the oven is 2torr, close the vacuum valve and vacuum pump; cure under vacuum conditions until the moisture on the surface of the wet blank is completely dry.
[0132] The mass of the initiator is about 0.094% of the slurry raw material, and the mass of the catalyst is about 0.02% of the slurry raw material.
[0133] S5: Dry.
[0134] After demoulding, the wet blank was placed in a container with a 55% ethanol solution, placed at room temperature for 6 hours, and the solution was poured out; the same volume of 75% ethanol solution was added again, placed at room temperature for 2 hours, and then placed in an oven and heated to 40°C, dried until the weight loss was 50%, and the wet blank was taken out and placed in a constant temperature and humidity chamber, the temperature was set to 30°C, and dried for 10 minutes at a humidity of 90% RH until the ethanol was completely volatilized. The ratio of the mass of the ethanol solution used each time to the mass of the wet blank was 1.42:1.
[0135] S6: Debinding.
[0136] The completely dried green body was placed in a muffle furnace, the heating rate was set to 3°C / min, and it was kept at 340°C for 3 hours; then, the furnace temperature was increased to 550°C at 1°C / min and kept for 3 hours; the furnace temperature was then increased to 800°C at 1°C / min and kept for 3 hours; finally, the furnace was cooled.
[0137] S7: Sintering.
[0138] The green body was placed in a gas pressure sintering furnace, nitrogen atmosphere was introduced, the pressure was set to 2MPa, the temperature was raised from room temperature to 1000℃ at 5℃ / min, and kept at this temperature for 3h; from 1000℃ to 1425℃ at 6℃ / min, and kept at this temperature for 3h; then, the temperature was raised to 1600℃ at 3℃ / min, and kept at this temperature for 2h; then, the temperature was raised to 1780℃ at 1℃ / min, and kept at this temperature for 5h. After sintering, the temperature was lowered to 1000℃ at 2℃ / min, and finally cooled to room temperature with the furnace.
[0139] S8: Grind and vibrate-polish the sample to obtain a finished ceramic thin plate.
[0140] Example 2
[0141] The difference between this embodiment and embodiment 1 is that in S5, after demolding the wet blank, it is placed in a container containing a 45% ethanol solution, left at room temperature for 6 hours, and the solution is poured out; an equal volume of 60% ethanol solution is added again, left at room temperature for 2 hours, and then placed in an oven, heated to 40°C, and dried to a weight loss of 50%; the wet blank is taken out, placed in a constant temperature and humidity chamber, the temperature is set to 30°C, and dried at a humidity of 90% RH for 10 minutes until the ethanol is completely volatilized.
[0142] The remaining steps and conditions are the same as those in Example 1.
[0143] Example 3
[0144] The difference between this embodiment and embodiment 1 is that in S5, after demolding the wet blank, it is placed in a container containing a 30% ethanol solution, left at room temperature for 6 hours, and the solution is poured out; an equal volume of 45% ethanol solution is added again, left at room temperature for 2 hours, and then placed in an oven, heated to 40°C, and dried to a weight loss of 50%; the wet blank is taken out, placed in a constant temperature and humidity chamber, the temperature is set to 30°C, and dried at a humidity of 90% RH for 10 minutes until the ethanol is completely evaporated.
[0145] The remaining steps and conditions are the same as those in Example 1.
[0146] Example 4
[0147] The difference between this embodiment and embodiment 1 is that in S4, the vacuum degree in the box is adjusted to 6 torr.
[0148] The remaining steps and conditions are the same as those in Example 1.
[0149] Example 5
[0150] The difference between this embodiment and embodiment 1 is that in S4, the vacuum degree in the box is adjusted to 10 torr.
[0151] The remaining steps and conditions are the same as those in Example 1.
[0152] Example 6
[0153] The difference between this embodiment and embodiment 1 is that in S7, the pressure is set to 4 MPa.
[0154] The remaining steps and conditions are the same as those in Example 1.
[0155] Example 7
[0156] The difference between this embodiment and embodiment 1 is that in S7, the pressure is set to 6 MPa.
[0157] The remaining steps and conditions are the same as those in Example 1.
[0158] Example 8
[0159] The difference between this embodiment and embodiment 1 is that in S2, the amounts of dibutyl phthalate, tributyl acetyl citrate and deionized water are replaced with 1.21 g, 2.65 g and 24.92 g respectively.
[0160] In this embodiment, the mass of the premix is 34.71 g, the mass of the slurry raw material is 148.22 g, the powder raw material is about 76.58% of the slurry raw material; the mass of the organic monomer is about 14.41% of the premix liquid, and the mass of the plasticizer is about 2.60% of the slurry raw material.
[0161] The remaining steps and conditions are the same as those in Example 1.
[0162] Example 9
[0163] The difference between this embodiment and embodiment 1 is that in S2, the amounts of dibutyl phthalate, tributyl acetyl citrate and deionized water are replaced with 1.48 g, 3.27 g and 24.03 g respectively.
[0164] In this embodiment, the mass of the premix is 34.71 g, the mass of the slurry raw material is 148.22 g, the powder raw material is about 76.58% of the slurry raw material; the mass of the organic monomer is about 14.41% of the premix liquid, and the mass of the plasticizer is about 3.20% of the slurry raw material.
[0165] The remaining steps and conditions are the same as those in Example 1.
[0166] Example 10
[0167] The difference between this embodiment and embodiment 1 is that in S4, the amounts of benzoyl peroxide and tetramethylethylenediamine are replaced with 0.11 g and 0.09 g, respectively.
[0168] In this embodiment, the mass of the initiator is about 0.074% of the slurry raw material, and the mass of the catalyst is about 0.06% of the slurry raw material.
[0169] The remaining steps and conditions are the same as those in Example 1.
[0170] Embodiment 11
[0171] The difference between this embodiment and embodiment 1 is that in S2, the amounts of benzoyl peroxide and tetramethylethylenediamine are replaced with 0.07 g and 0.15 g, respectively.
[0172] In this embodiment, the mass of the initiator is about 0.047% of the slurry raw material, and the mass of the catalyst is about 0.1% of the slurry raw material.
[0173] The remaining steps and conditions are the same as those in Example 1.
[0174] The green ceramic sheets of Examples 1 to 11 above have no obvious deformation or warping, and the prepared ceramic sheets have high flatness.
[0175] Comparative Example 1
[0176] The difference between this comparative example and Example 1 is that the curing method in S4 is replaced by placing it in a cool place for natural curing until the moisture on the surface of the wet blank is completely dissipated; the remaining steps and conditions are the same as in Example 1.
[0177] In this comparative example, after the sample was cured, obvious stratification occurred on the surface, and the part of the surface where no gel was formed cracked and peeled off on a large scale, and slight warping occurred after subsequent drying.
[0178] Comparative Example 2
[0179] The difference between this comparative example and Example 1 is that in S5, the wet blank is demolded and placed at room temperature until the wet blank is completely dried; the remaining steps and conditions are the same as those in Example 1.
[0180] In this comparative example, the sample showed slight stratification on the surface after curing, and a small amount of cracks appeared on the surface where no gel was formed, but it did not peel off; after subsequent drying, more serious deformation and warping occurred, and the stratified part of the surface peeled off.
[0181] Comparative Example 3
[0182] The difference between this comparative example and Example 1 is that: in S5, the wet blank is demolded and placed in a constant temperature and humidity chamber, the temperature is set to 30°C, and the humidity is 90% RH for 72 hours; in S6, the completely dried green blank is placed in a muffle furnace, the heating rate is set to 0.5°C / min, and it is kept at 340°C for 3 hours; then, the furnace temperature is increased to 550°C at 0.5°C / min and kept at this temperature for 3 hours; the furnace temperature is then increased to 800°C at 1°C / min and kept at this temperature for 3 hours; finally, the furnace is cooled; the remaining steps and conditions are the same as in Example 1.
[0183] In this comparative example, the sample did not show deformation or warping after drying and debinding.
[0184] Comparative Example 4
[0185] The difference between this comparative example and Example 1 is that the mass of the initiator is 0.02% of the slurry raw material.
[0186] Comparative Example 5
[0187] The difference between this comparative example and Example 1 is that the mass of the initiator is 0.15% of the slurry raw material.
[0188] Comparative Example 6
[0189] The difference between this comparative example and Example 1 is that the mass of the catalyst is 0.01% of the slurry raw material.
[0190] Comparative Example 7
[0191] The difference between this comparative example and Example 1 is that the mass of the catalyst is 0.15% of the slurry raw material.
[0192] Comparative Example 8
[0193] The difference between this comparative example and Example 1 is that the mass of the plasticizer is 4% of the slurry raw material.
[0194] Test example
[0195] The ceramic thin plates prepared in Examples 1 to 11 and Comparative Examples 1 to 8 were tested for performance, wherein the flexural strength was tested by the three-point bending method according to ISO 23242:2020; the fracture toughness was tested by the single-sided V-notch plate method according to ISO 21113:2018; the hardness was measured by a microhardness tester according to GB / T 16534-2009; and the time required for the surface of the slurry to be free of moisture after the slurry changes from a liquid state to a gel state was recorded as the curing time. The results are shown in Table 1.
[0196] Table 1 Test results
[0197]
[0198]
[0199] It can be seen from Table 1 that the ceramic thin plate prepared in the embodiment of the present invention has high bending strength, fracture toughness and hardness, and the curing time is controllable.
[0200] Among them, when the performance is not much different, the drying method of comparative example 3, in which the wet blank is directly placed in a constant temperature and humidity chamber, has a longer drying cycle (up to 72 hours) and a higher time cost.
[0201] In Comparative Example 6, the amount of catalyst added was too low, resulting in an extremely slow reaction between the organic monomer and the crosslinking agent, and a polymer network could not be formed; conversely, the amount of catalyst added in Comparative Example 7 was too high, resulting in a rapid reaction between the organic monomer and the crosslinking agent to form a polymer network, and the cured gel could not be poured out of the container.
[0202] In Comparative Example 8, since more plasticizer is added than in other embodiments, the gel curing time is prolonged, thereby reducing the mechanical properties of the sample. Specifically, as the amount of tetramethylethylenediamine added increases, the gelling reaction rate increases, a large number of monomer free radicals are generated instantly, and the formed polydimethylacrylamide macromolecular chain is shorter, the internal stress of the blank is smaller, and the mechanical properties are better; conversely, the longer the curing time, the lower the mechanical properties of the blank.
[0203] In summary, the method provided by the present invention can obtain a ceramic thin plate with high flatness, high bending strength, fracture toughness and hardness. In addition, the method can realize rapid pulling of the upper mold 200, improve demolding efficiency, and reduce production costs.
[0204] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a ceramic thin plate, characterized in that: The following steps are involved: The raw materials for preparing the ceramic sheet are injected into the mold, followed by curing, demoulding, drying, debinding and sintering; The raw materials for preparation include slurry raw materials, initiators and catalysts; the slurry raw materials include powder raw materials and premixed liquids; the powder raw materials include ceramic powders and sintering aids; the premixed liquid includes organic monomers, crosslinking agents, dispersants, plasticizers and solvents; The mass of the powder raw material is 60% to 77% of the slurry raw material; The mass of the sintering aid in the powder raw material is 2% to 7%, and the balance is the ceramic powder; The mass of the organic monomer is 14% to 25% of the premixed liquid, the mass ratio of the organic monomer to the crosslinking agent is 20:1 to 70:1, the mass of the dispersant is 0.5% to 1.6% of the powder raw material, and the mass of the plasticizer is 2% to 3.3% of the slurry raw material; The mass of the initiator is 0.045% to 0.096% of the slurry raw material, and the mass of the catalyst is 0.020% to 0.102% of the slurry raw material.
2. The preparation method according to claim 1, characterized in that: The ceramic powder includes at least one of silicon nitride, silicon carbide, aluminum oxide, aluminum nitride, iron oxide, chromium oxide and zirconium oxide; and / or, the sintering aid comprises at least one of magnesium oxide, yttrium oxide, titanium oxide, silicon oxide, calcium oxide and strontium oxide; and / or, the organic monomer comprises at least one of dimethylacrylamide, acrylamide, methacrylamide and hydroxymethylacrylamide; and / or, the cross-linking agent comprises at least one of methylene acrylamide, methyl acryl acrylate and poly(ethylene glycol) dimethacrylate; and / or, the dispersant comprises at least one of ammonium polyacrylate, polyethylene glycol, citrate, polyetherimide, diethylene glycol, ethylene glycol ethyl ether, sodium lauryl sulfate, sodium hexametaphosphate and polyvinyl pyrrolidone; and / or, the plasticizer comprises at least one of phthalates, stearates and citrates; and / or, the initiator comprises at least one of ammonium persulfate, benzoyl peroxide, tert-butyl hydroperoxide and azobisisobutyronitrile; And / or, the catalyst includes at least one of tetramethylethylenediamine, β-naphthalenesulfonic acid formaldehyde condensation product and 2,2'-azo[2-(2-imidazolin-2-yl)propane]dihydrochloride.
3. The preparation method according to claim 1, characterized in that: The preparation of the powder raw material comprises: wet ball milling a mixture of ceramic powder and sintering aid, and drying; Preferably, the ball milling speed is 200 r / min to 320 r / min, and the ball milling time is 15 h to 24 h; Preferably, the mixture of the ceramic powder and the sintering aid is first subjected to a first wet ball milling and a first drying, then sintered, and then subjected to a second wet ball milling and a second drying; Preferably, the sintering temperature is 1000° C. to 1300° C., and the sintering time is 3 h to 5 h.
4. The preparation method according to claim 1, characterized in that: The preparation of the slurry raw material includes: mixing part of the powder raw material with the premixed liquid for the first time and degassing, and then adding the remaining powder raw material for the second time and degassing; Preferably, the first mixing is carried out at 1150 r / min to 1450 r / min for 3 min to 5 min; Preferably, the second mixing is carried out at 1500 r / min to 1800 r / min for 5 min to 8 min; Preferably, the powder raw materials used in the first mixing account for 1 / 2 to 2 / 3 of all the powder raw materials.
5. The preparation method according to claim 1, characterized in that: The mold comprises an upper mold and a lower mold that match each other; The lower mold is provided with a groove, and the upper mold is provided with a through hole, so that after the upper mold and the lower mold are molded together, the groove and the through hole cooperate to form a pouring cavity for accommodating the prepared raw material, and the open part of the through hole away from the groove is used to inject the prepared raw material; Preferably, the roughness of the surface of the lower mold for contacting the raw material is 2.1 μm to 5.8 μm, the roughness of the surface of the lower mold for contacting the upper mold is 7.3 μm to 13.2 μm; the roughness of the surface of the upper mold for contacting the lower mold is 7.3 μm to 13.2 μm; Preferably, the groove wall of the groove has a smooth hydrophobic layer.
6. The preparation method according to claim 1, characterized in that: The curing is carried out at 28°C to 42°C and 1 torr to 10 torr for 6 to 12 minutes.
7. The preparation method according to claim 1, characterized in that: Drying includes: using a liquid desiccant to dehydrate the wet blank obtained by demoulding; Preferably, the liquid desiccant comprises at least one of polyethylene glycol, ethanol, acetone, glycerol, 1,2-propylene glycol and diethylene glycol; Preferably, the wet blank is first placed in the first liquid desiccant for 2h to 6h, and then placed in the second liquid desiccant for 2h to 6h, and then the liquid desiccant is removed to obtain a green blank; wherein the concentration of the first liquid desiccant is less than the concentration of the second liquid desiccant; Preferably, the ratio of the mass of the liquid desiccant used in each drying to the mass of the wet blank is 1.21:1 to 2.47:
1.
8. The preparation method according to claim 1, characterized in that: Debinding includes: First, carry out the process at 230℃~340℃ for 2h~3h, then at 500℃~625℃ for 2h~3h, then at 780℃~820℃ for 2h~3h; finally, cool down with the furnace; Preferably, the temperature is increased to 230°C to 340°C at a heating rate of 1°C / min to 3°C / min; Preferably, the temperature is increased to 500° C. to 625° C. at a heating rate of 0.5° C. / min to 1° C. / min.
9. The preparation method according to claim 1, characterized in that: Sintering is carried out at 2MPa to 6MPa; Preferably, the sintering atmosphere is a vacuum or an inert atmosphere.
10. A ceramic thin plate, characterized in that: Prepared by the preparation method according to any one of claims 1 to 9; Preferably, the thickness of the ceramic thin plate is ≤3 mm; Preferably, the flexural strength of the ceramic thin plate is not less than 675 MPa; Preferably, the fracture toughness of the ceramic sheet is not less than 5.74 MPa·m 1 / 2 ; Preferably, the hardness of the ceramic thin plate is not less than 17.60 GPa.
Citation Information
Cited By
Breakthrough-resistant multilayer ceramic substrate and preparation method thereof
CN120887709A